Acceleration of Storage Performance in Cloud Systems by Using NVRAM - Jisun Kim; Yunjoo Park; Kyungwoon Cho; Hyokyung Bahn (Journal of ICT, Design, Engineering and Technological Science, 2019)
Non-Volatile Random Access Memory (NVRAM) is anticipated to be utilized as the performance accelerator of future cloud storage systems. This article aims to analyze how large performance improvement can be expected if we use NVRAM as the performance accelerator of legacy storage subsystems. Specifically, we try to find the best employment of NVRAM with respect to storage performances. To do so, we quantify the hot storage area and replace it with NVRAM to obtain the best performances. Our analysis shows that the source of hot storage traffic is not limited to any single particular storage area, but it is different for application types executed. Specifically, journaling accesses dominate in database applications, while swapping accesses dominate in memory-intensive applications. In some applications such as video streaming, file accesses dominate. Based on these findings, we suggest the usage of NVRAM to maximize the performance improvement of cloud storage systems.